The extent to which health insurance indicates the efficiency of healthcare centers in KSA - Nasrulddin, Vivian Mohammed Saleh; Alnahdi, Amal Ghazi; Bokhari, Esraa Ahmad (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to analyze the extent to which health insurance indicates the efficiency of health care centers in the Kingdom of Saudi Arabia during the period (2005-2021). For this purpose, an Autoregressive Distributed Lag Model (ARDL) has been described, to express the relationship between the number of patients’ visits to health centers as a dependent variable and between the independent variables associated with health insurance, which were chosen based on previous studies and researchers’ efforts, represented in each of the following: average per capita income, depth of insurance index, gross written premiums, insurance retention index, and population estimates. By specifying the variables and hypotheses to be tested, descriptive tests were conducted, and the general trend of the variables was identified by the statistical program E-views. In the long term, the study showed an inverse relationship between the dependent variable and each of: average income, insurance depth index, total written insurance premiums, and insurance retention index. The study also showed that the population estimates did not affect the number of patients’ visits to health centers. In the short term, the study showed a direct relationship between the dependent variable and each of: the average per capita income, depth of insurance index, and the gross written premiums, while it concluded that the number of patients’ visits to health centers was not affected by: the insurance retention index and population estimates.